The research on AP1000 nuclear main pumps' complete characteristics and the normalization method. (January 2017) - Zhu, Rongsheng; Liu, Yong; Wang, Xiuli; Fu, Qiang; Yang, Ailing; Long, Yun
Highlights: Complete characteristics of main pump are researched into. The quadratic character of head and torque under some operatings. The characteristics tend to be the same under certain conditions. The normalization method gives proper estimations on external characteristics. The normalization method can efficiently improve the security computing. Abstract: The paper summarizes the complete characteristics of nuclear main pumps based on experimental results and makes a detailed study, and then draws a series of important conclusions: with regard to the overall flow area, the runaway operating and 0-revolving-speed operating of nuclear main pumps both have quadratic characteristics; with regard to the infinite flow, the braking operation and the 0-revolving-speed operation show consistent external characteristics. To remedy the shortcomings of the traditional complete-characteristic expression with regards to only describing limited flow sections at specific revolving speeds, the paper proposes a normalization method. As an important boundary condition of the security computing of unstable transient process of the primary reactor coolant pump and the nuclear island primary circuit and secondary circuit, the precision of complete-characteristic data and curve impacts the precision of security computing. A normalization curve obtained by applying the normalization method to process complete-characteristic data could correctly, completely and precisely express the complete characteristics of the primary reactor coolant pump under any rotational speed and full flow, and is capable of giving proper estimations on external characteristics of the flow outside the test range and even of the infinite flow. These advantages are of great significance for the improvement of security computing of transient processes of the primary reactor coolant pump and the circuit system.